Порівняльний аналіз фреймворків PHP - Ходонович, А. Б. (ХНУРЕ, 2024)
The research aims to analyze various PHP frameworks with a focus on Laravel and Symfony, with an overview of their advantages and disadvantages. Laravel is characterized by simplicity and a powerful ORM, while Symfony is characterized by high performance and modularity. The pros and cons analysis show that Symfony is suitable for complex large applications, while Laravel is effective for quickly implementing small projects
Keywords: аналіз фреймворків PHP; PHP frameworks